(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study is descriptive qualitative. The sample of this study was sixth semester students in English department of STKIP Abdi Pendidikan Payakumbuh. There were 31 students. The writer choose the sample by using purposive sampling technique. The instrument of this study was the questionnaire which was consist of 30 items based on survey of reading strategy developed by Mokhtary and Sheorey in 2002. Based on data analysis the data can be shown as follow: in using Global Strategy; 8.44% students chose always, 36.22% students chose often, 43.67% students chose sometime, 10.91% students chose seldom and 0.74% students chose never. Meanwhile, in using problem solving Strategy; 12.91% students chose always, 43.15% students chose often, 38.737% students chose sometime, 3.63% students chose seldom and 1.61% students chose never. Last, in using support strategy; 15.43% students chose always, 36.2% students chose often, 35.12% students chose sometime, 11.83% students chose seldom and 1.43% students chose never. Based on the data, it can be concluded that metacognitive strategy in reading comprehension applied by the students were Support strategy and then followed by Problem – solving strategy and Global strategy. Keywords: metacognitive strategy, reading comprehension, STKIP students